Soil and water contamination - Perk, Marcel Van Der (CRC Press, 2014)
This comprehensive, successful textbook, now in its second edition, has been conscientiously updated and extended and includes many case studies, examples and exercises sections, providing undergraduate and graduate students in the Earth and Environmental Sciences with all the material necessary for the study of soil and water contamination. In addition, it can serve as a useful source of information for professionals